A single dose of erythropoietin reduces perioperative transfusions in cardiac surgery: results of a prospective single‐blind randomized controlled trial. Issue 7 (23rd February 2015) - Weltert, Luca; Rondinelli, Beatrice; Bello, Ricardo; Falco, Mauro; Bellisario, Alessandro; Maselli, Daniele; Turani, Franco; De Paulis, Ruggero; Pierelli, Luca
<x xml:space="preserve">Abstract</x> BACKGROUND We conducted a prospective single‐blind randomized study to assess whether a single 80, 000 IU dose of human recombinant erythropoietin (HRE), given just 2 days before cardiac surgery, could be effective in reducing perioperative allogeneic red blood cell transfusion (aRBCt). STUDY DESIGN AND METHODS Six‐hundred patients presenting with preoperative hemoglobin (Hb) level of not more than 14.5 g/dL were randomly assigned to either HRE or control. The primary endpoint was the incidence of perioperative aRBCt. The secondary endpoints were mortality and the incidence of adverse events in the first 45 days after surgery, Hb level on Postoperative Day 4, and number of units of RBC transfusions in the first 4 days after surgery. RESULTS A total of 17% (HRE) versus 39% (control) required transfusion (relative risk, 0.436; p < 0.0005). After baseline Hb was controlled for, there was no difference in the incidence of aRBCt between HRE (0%) and control (3.5%) among the patients with baseline Hb of 13.0 g/dL or more, which included the nonanemic fraction of the study population. The mean (range) Hb level on Postoperative Day 4 was 10.2 (9.9‐10.6) g/dL (HRE) versus 8.7 (8.5‐9.2) g/dL (control; p < 0.0005). The distribution of number of units transfused was shifted toward fewer units in HRE (p < 0.0005). The all‐cause mortality at 45 days was 3.00% (HRE) versus 3.33% (control). The 45‐day adverse event rate was 4.33% (HRE) versus 5.67% (control; both p = NS). CONCLUSION In anemic patients (Hb < 13 g/dL), a single high dose of HRE administered 2 days before cardiac surgery is effective in reducing the incidence of aRBCt without increasing adverse events.